Implementasi Kebijakan Publik Berbasis Gender Melalui Program Sekolah Ramah Anak - Christine Diah Wahyuningsih; Desy Ambarwati (Public Service and Governance Journal, 2026)
This study aims to analyze the implementation of gender-based public policy through the Child-Friendly School Program at SDN 01 Bendosari, Plantungan District, Kendal Regency. This research employed a descriptive qualitative approach using in-depth interviews, observation, and documentation as data collection techniques. Data analysis was conducted using the public policy implementation model proposed by George C. Edwards III, which emphasizes four key variables: communication, resources, implementers’ disposition, and bureaucratic structure. The findings reveal that the implementation of the Child-Friendly School policy at SDN 01 Bendosari has been carried out through an integrative approach by incorporating child-friendly principles into existing school programs and culture. Effective policy communication and positive implementers’ disposition, particularly among teachers and the school principal, have supported the implementation process. However, limited financial resources remain a major obstacle to fully optimizing the policy implementation. This study concludes that successful public policy implementation depends not only on regulatory frameworks but also on resource availability, implementers’ commitment, and institutional capacity to adapt policies to local conditions.